Surveillance society in a digitalized world - AL, EYÜP (IGI Global, 2022)
Although the surveillance society discussions have been carried out for a long time, they have recently moved to a different stage with the increase of digitalization. There is a new situation that changes the entire historical context of surveillance, and this new situation is briefly called digital surveillance. However, to make sense of digitalization and digital surveillance, it is necessary to explain how digital citizenship contributes to this process. Digitalization without digital citizenship is unthinkable. In short, this study will show the continuities and breaks of the phenomenon of surveillance in the historical pro- cess by shifting from classic surveillance practices to digital surveillance forms. Digital surveillance is considered to be much more complex, sophisticated, incomprehensible to all, and transcends all kinds of time and space boundaries compared to classic surveillance.
Keywords: Sosyal ve Beşeri Bilimler; Kitle İletişimi ve Araçları; İletişim Bilimleri; Radyo, Sinema ve Televizyon; Social Sciences and Humanities; Mass Communications and Mass Media; Communication Sciences; Radio, Cinema and Television; Sosyal Bilimler (SOC); Sosyal Bilimler Genel; İLETİŞİM; FİLM, RADYO, TELEVİZYON; Social Sciences (SOC); SOCIAL SCIENCES, GENERAL; COMMUNICATION; FILM, RADIO, TELEVISION; İletişim; Sosyal Bilimler ve Beşeri Bilimler; Communication; Social Sciences & Humanities